Peran Guru Penggerak dalam Mensukseskan Kurikulum Merdeka di SMK Negeri 1 Solok - Sari, Yulia Nita; Ikhwan, Ikhwan (Jurusan PIPS FKIP UMMY Solok, 2023)
Abstract This research is motivated by the motivating teacher who can encourage learning that supports students, by collaborating with fellow teachers in realizing independent learning. The aim of this research is to analyze the role of driving teachers in making the independent curriculum a success at SMK Negeri 1 Solok. The research method used is qualitative with a descriptive approach. The subjects in this research were driving teachers, assistant driving teachers, teachers, school principals, curriculum representatives, and students of SMKN 1 Solok. Data collection was carried out through interviews, observation and documentation. Based on the results of the interview, it can be concluded that the driving teacher collaborates with the practice assistant to mobilize fellow teachers through a collaboration space called PADI. In PADI, driving teachers will carry out coaching and discuss with fellow teachers, to create learning that supports students which is in accordance with the independent curriculum. The aim of this collaboration is so that teachers can provide assistance and inspire students to achieve the best achievements in the learning process.